A review of intraoperative protective ventilation - Zou, Yuanyuan; Liu, Zhiyun; Miao, Qing; Wu, Jingxiang (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2024)
Mechanical ventilation is an important life-saving therapy for general anesthesia and critically ill patients, but ventilation itself may be accompanied with lung injury. Ventilator-induced lung injury (VILI) exacerbates pre-existing lung disease, leading to poor clinical outcomes. Especially for patients undergoing cardiothoracic surgery and receiving one-lung ventilation (OLV), optimizing the parameters of OLV is closely related to their prognosis. It is not clear what is the best strategy to minimize VILI through adjusting ventilation parameters, including tidal volume, positive end expiratory pressure and driving pressure, etc. Different parameters, in combination, are responsible for VILI. Protective ventilation strategies, aiming to reduce postoperative pulmonary complications, have been discussed in many clinical studies and different opinions have been raised. This review addresses the pathogenesis of VILI and focus on the OLV management and better protective OLV strategies during thoracic surgery.